In vitro selection and characterization of RNA aptamers binding thyroxine hormone - Lévesque, Dominique (Portland Press Ltd., 2007)
RNA possesses the ability to bind a wide repertoire of small molecules. Some of these binding interactions have been shown to be of primary importance in molecular biology. For example, several classes of mRNA domains, collectively referred to as riboswitches, have been shown to serve as RNA genetic control elements that sense the concentrations of specific metabolites (i.e. acting as direct sensors of chemical compounds). However, to date no RNA species binding a hormone has been reported. Here, we report that the use of an appropriate SELEX (systematic evolution of ligands by exponential enrichment) strategy results in the isolation of thyroxine-specific aptamers. Further biochemical characterization of these aptamers, including mutational studies, the use of transcripts with site-specific modified nucleotides, nuclease and chemical probing, binding-shift assays and CD, demonstrated that these RNA structures included a G-rich motif, reminiscent of a guanine quadruplex structure, adjacent to a helical region. The presence of the thyroxine appeared to be essential for the formation of the structural motif's scaffold. Moreover, the binding is shown to be specific to thyroxine (T4) and tri-iodothyronine (T3), the active forms of the hormone, whereas other inactive derivatives, including thyronine (T0), do not support complex formation. These results suggest that this aptamer specifically binds to the iodine moieties of the thyroxine, a previously unreported ability for an RNA molecule.